Total coumarins from fruits of Cnidium monnieri inhibit formation and differentiation of multinucleated osteoclasts of rats. - Qin Lu-Ping; Zhang Qiao-Yan; Tian Ye-Pin; Zheng Han-Chen; Huang Mao; Huang Bao-Kang (Acta Pharmacologica Sinica, 2016)
AIM: To determine the effects of TCFC (total comarins from the fruits of Cnidium monnieri) on the activity of osteoclasts in vitro. METHODS: Osteoclasts isolated from rat marrow cells were co-cultured with osteoblasts under the 1,25-dihydroxyvitamine D3. The tartrate-resistant acid phosphatase (TRAP) stain was used to identify osteoclast morphology. The activity of TRAP was measured by p-nitrophenyl sodium phosphate assay. The resorption pit area on the bone slices formed by osteoclasts was measured by computer image processing. Calcium concentration in the medium of co-culture of bone slices and osteoclasts was determined by atomic absorption spectra. RESULTS: TCFC 2.5-25 mg/L inhibited osteoclast formation and differentiation. TCFC 0.25-25 mg/L inhibited TRAP activity of osteoclasts and TCFC 25 mg/L decreased the TRAP activity by 26.3 % and 24.1 % after 48 h and 72 h, respectively. TCFC 25 mg/L decreased the osteoclastic bone resorption pit area by 25.05 % and Ca2+ release from bone slices by 41.73 %. CONCLUSION: TCFC reduced the bone lose by decreasing the osteoclast formation, its TRAP activity, and osteoclastic bone resorption.